The children we sacrifice - Poore, Grace; Harmon, Daisette; Lee, Penny; Dattar, Narendra; SHaKTI Productions; Women Make Movies (firm) (New York : Distributed by Woman Make Movies, 1999)
Incestuous sexual abuse of young girls in South Asia is a subject traditionally shrouded in secrecy. through survivors narratives and interviews with health professionals, this film discloses the many layers of sexual abuse and the far-reaching psychological, social and cultural consequences of incest
Camera, Daisette Harmon ; editors, Penny Lee, Grace Poore ; vocal music, Narendra Datar
Keywords: Incest -- South Asia; Child abuse, Sexual -- South Asia; Incest victims -- South Asia -- Interviews; Psychotherapists -- South Asia -- Interviews